2018
DOI: 10.1089/aid.2017.0238
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Non-B HIV-1 Subtypes in Overseas Sailors and Prostitutes in Korea

Abstract: There have been no studies related to groups at the highest risk for HIV-1 infection in Korea before 1993. In this study, for the first time, we report the distribution of HIV subtypes in overseas sailors (OSs) and prostitutes who worked in brothels near U.S. military bases in Korea. We retrospectively determined the sequences of nef in 131 patients using reverse transcription polymerase chain reaction (RT-PCR). These patients composed of 102 OSs, 14 OS spouses, and 15 prostitutes. Phylogenetic analysis was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Among the 876 infected individuals reported from 1985 to 1998, OSs accounted for 18.4% 1 . Previous studies have shown that 80% of patients in these groups and their partners were infected with non-B subtype viruses 5 , 6 .…”
Section: Introductionmentioning
confidence: 98%
“…Among the 876 infected individuals reported from 1985 to 1998, OSs accounted for 18.4% 1 . Previous studies have shown that 80% of patients in these groups and their partners were infected with non-B subtype viruses 5 , 6 .…”
Section: Introductionmentioning
confidence: 98%
“…Since 1988, Korean OSs had undergone compulsory testing for anti-HIV-1 antibody [17]. If each OS returns to Korea once every 2 or 3 years, the time of primary infection can be estimated relatively precisely in conjunction with previous negative results for anti-HIV-1 antibody.…”
Section: Resultsmentioning
confidence: 99%
“…4 and 5). In 1988–1992, various non-B subtypes were transmitted to Korea through OSs [17]. As some of these were homosexual, recombinant strains of KSB and non-B may have arisen, as in patient 92-65, who was infected with subtype D based on the nef gene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations